Do we Have the Gut to Beat Thrombosis? - Tsante, Konstantina; Petrou, Eleni; Tsalas, Stavros; Tsantes, Andreas G.; Lianou, Alexandra; Kartelias, Georgios; Kyriakou, Elias; Kokoris, Styliani; Nikolopoulos, Georgios; Bonovas, Stefanos; Sokou, Rozeta (Seminars in Thrombosis and Hemostasis, 2025)
Arterial and venous thromboembolism represent major contributors to global morbidity and mortality. Despite substantial progress in risk stratification and clinical management, a significant proportion of thromboembolic events occur in individuals not classified within traditional high-risk groups indicating the involvement of additional, non-conventional risk factors in thrombotic pathophysiology.Recent evidence has highlighted the gut microbiome as a critical determinant of human health, with increasing recognition of its role in cardiovascular and thrombotic disorders. Furthermore, the gut microbiome constitutes a modifiable risk factor, offering new horizons for therapeutic intervention and emerging evidence suggests that alterations in the microbiome may significantly impact thrombotic risk.Moreover, microbiome-derived metabolites have gathered considerable scientific attention for their potential involvement in the initiation and progression of thrombosis. These metabolites may serve as novel biomarkers, complementing conventional risk indicators in disease diagnosis, prognosis, screening, and patient monitoring. Microbiome-derived metabolites may hold dual utility, first as diagnostic and prognostic biomarkers, and, second, as potential targets for pharmacologic modulation. Collectively, these findings underscore the growing significance of the gut microbiome as an environmental factor in thromboembolic disease and justify the constantly increasing employment of the scientific community in several aspects of health and disease.
Keywords: gut microbiome; microbiota; thrombosis; cardiovascular disease; TMAO